Cross-Cultural Challenges in Indonesian Workplaces: A Systematic Literature Review of Chinese Expatriate Adaptation in Companies in Indonesia - Kristanti, Pingki; Prasetya, Andika; Prayogo, Ahmat; Anshori, Mochammad; Safrizal, Helmi (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The growing number of Chinese expatriates in Indonesian companies has become an interesting subject for academics and business practitioners in cross-cultural management studies. The increasing number of Chinese workers entering Indonesia will make them experience barriers in communication. The existence of communication barriers when adapting will certainly have the potential for misunderstanding and even conflict. The way expatriates adapt to the new environment is something that needs to be considered, with differences in ethics and culture, it is feared that it can become a conflict in the business world. This research was conducted using the Systematic Literature Review (SLR) method, a research method used to identify, analyze, evaluate, and interpret all previous research results obtained by researchers. The selected literature contained six articles that were in accordance with the research topic. The literature obtained discusses conflicts that often occur between Chinese workers and local workers due to cultural differences, such as differences in terms of work ethic, discipline, and non-verbal styles that can cause misunderstanding.